The Effect of Nanostructured Functional Ceramics Additives on the Properties of Welding Electrodes - Saidov Mannapovich Rustam; Rakhimov Khakimovich Rustam; Kamel Touileb (Metals, 2023)
The present work aimed to develop a new coated electrode weld based on ceramic materials. Photocatalysts of nanostructured functional ceramics (PNFCs) were synthesized by means of concentrated solar radiation on ceramic materials. This new process allows the efficient conversion of the energy of the primary source into pulsed radiation, through the adjustable and judicious choice of parameters. The photocatalysts also showed high activity when they were introduced into an electrode coating. The main problem is the complexity of the production of NFC photocatalysts on an industrial scale. A new method was developed for producing ZB-1-grade NFC catalysts using conventional technology, with subsequent activation via pulsed radiation generated by functional ceramics. The results of the addition of NFC photocatalysts obtained using this technology on the welding and technological properties of welding electrodes of the MR-3 brand are presented. The introduction of 1% to 8% NFC of the ZB-1 grade into the coating enhanced the stability of arc burning (Lbla) and increased the diameter of the weld point (ødp.). Moreover, the addition of 1% to 8% NFC of the ZB-1 brand into the coating contributed to a reduction in the losses factor for waste and splashing of electrode metal (ψ) leading to a reduction in the height of the visor at the end of the electrode (hk).